In utero and lactational exposure to tenofovir disoproxil fumarate and bone health outcomes: a scoping review of 31 studies - Xia Ji; Yuanzhong Wang; Zefan Zhang; Kok-Lun Pang; Xiong Khee Cheong; Norliza Muhammad; Kok-Yong Chin (Frontiers in Endocrinology, 2026)
Introduction Tenofovir disoproxil fumarate (TDF) is a key antiretroviral agent for preventing mother-to-child transmission of human immunodeficiency virus (HIV) and treating chronic hepatitis B (HBV) during pregnancy. However, concerns persist regarding its potential effects on bone metabolism during foetal development and postpartum recovery. Objective This scoping review synthesised evidence on the impact of in utero and lactational TDF exposure on bone health in offspring and mothers. Methods A systematic search of PubMed, Scopus, Web of Science and the China National Knowledge Infrastructure identified randomised controlled trials, cohort studies, and observational studies assessing bone mineral density, bone mineral content, growth, or bone turnover markers in relation to perinatal TDF exposure. Thirty-one studies met the inclusion criteria. Results Most studies reported no clinically significant long-term effects of TDF on paediatric bone mineralisation, growth, or metabolism from infancy to mid-childhood. A transient reduction in neonatal bone mineral content was noted in a few studies, but its clinical relevance appeared limited. In contrast, TDF use in mothers was consistently associated with accentuated bone loss during pregnancy and lactation, particularly at the hip, with incomplete recovery postpartum, indicating potential long-term skeletal risk. Conclusions In utero and lactational exposure to TDF had minimal impact on paediatric bone development but was consistently linked to maternal bone loss and incomplete skeletal recovery. While the benefits of TDF in preventing vertical transmission of HIV and HBV outweigh these risks, the findings highlight the importance of ongoing monitoring of maternal bone health.